1999
DOI: 10.1093/emboj/18.6.1435
|View full text |Cite
|
Sign up to set email alerts
|

The high-resolution crystal structure of the molybdate-dependent transcriptional regulator (ModE) from Escherichia coli: a novel combination of domain folds

Abstract: The molybdate-dependent transcriptional regulator (ModE) from Escherichia coli functions as a sensor of molybdate concentration and a regulator for transcription of operons involved in the uptake and utilization of the essential element, molybdenum. We have determined the structure of ModE using multi-wavelength anomalous dispersion. Selenomethionyl and native ModE models are refined to 1.75 and 2.1 Å, respectively and describe the architecture and structural detail of a complete transcriptional regulator. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 46 publications
4
67
0
Order By: Relevance
“…This cleft is used by various proteins to engage RNA (61), DNA (46), oligosaccharides (62), proteins (63), and even metals and inorganic phosphates (64,65). For example, RPA, a eukaryotic recruiting and scaffolding protein critical to DNA replication, has been shown to bind both oligonucleotides and peptides through its six OB-fold domains (66 -70).…”
Section: Chemical Nature Of Mcm10-id Interactions With Dna Andmentioning
confidence: 99%
“…This cleft is used by various proteins to engage RNA (61), DNA (46), oligosaccharides (62), proteins (63), and even metals and inorganic phosphates (64,65). For example, RPA, a eukaryotic recruiting and scaffolding protein critical to DNA replication, has been shown to bind both oligonucleotides and peptides through its six OB-fold domains (66 -70).…”
Section: Chemical Nature Of Mcm10-id Interactions With Dna Andmentioning
confidence: 99%
“…At the C-terminal region of the ModE1 protein we found two transport-associated OB (DiMop) domains (residues 129 to 192 and 201 to 264) (Pfam 03459) similar to a molybdate-binding domain (MopI and MopII subdomains) ( Figure 1B) (Schultz et al, 1998;Letunic et al, 2006). This domain organization of the H. seropedicae ModE1 is similar to the E. coli ModE proteins (McNicholas et al, 1998b;Hall et al, 1999;Schüttelkopf et al, 2003;Studholme and Pau, 2003). To analyze the H. seropedicae ModE1 protein we constructed a plasmid to over-express ModE1 as a fusion to a His-tag sequence.…”
Section: Mode1 Proteinmentioning
confidence: 58%
“…It is known that E. coli ModE is a homodimer with a helix-turn-helix (HTH) DNA-binding motif at the N-terminal domain and a molybdate-binding site at the C-terminal DiMop domain, which is made up of two sub-domains in tandem that bind two molybdate ions per dimer at the domain interfaces (Hall et al, 1999;Schüttelkopf et al, 2003). Structural data have revealed that E. coli ModE discriminates between oxyanions based on size and charge, with the C-terminal domain undergoing a conformational change induced by the ligand which results in an alteration of the surface of the dimer and is a molecular switch regulating the recruitment of the partner proteins necessary for the positive regulation of transcription (Gourley et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…93) In addition to repression of the molybdate transporter operon, the ModE-molybdate complex activates at six operons encoding molybdate-containing enzymes and three operons encoding as yet unidenfied genes. 94) Typical ModE-binding site is composed of an inverted repeat of nona-nucleotides, CGnTATATA, with a spacer of hexanucleotides.…”
Section: Iron-sensing Regulatorsmentioning
confidence: 99%